Neuroinflammatory Process Involved in Different Preclinical Models of Chemotherapy-Induced Peripheral Neuropathy - Fumagalli, Giulia; Monza, Laura; Cavaletti, Guido; Rigolio, Roberta; Meregalli, Cristina (Frontiers in Immunology, 2021)
Peripheral neuropathies are characterized by nerves damage and axonal loss, and they could be classified in hereditary or acquired forms. Acquired peripheral neuropathies are associated with several causes, including toxic agent exposure, among which the antineoplastic compounds are responsible for the so called Chemotherapy-Induced Peripheral Neuropathy (CIPN). Several clinical features are related to the use of anticancer drugs which exert their action by affecting different mechanisms and structures of the peripheral nervous system: the axons (axonopathy) or the dorsal root ganglia (DRG) neurons cell body (neuronopathy/gangliopathy). In addition, antineoplastic treatments may affect the blood brain barrier integrity, leading to cognitive impairment that may be severe and long-lasting. CIPN may affect patient quality of life leading to modification or discontinuation of the anticancer therapy. Although the mechanisms of the damage are not completely understood, several hypotheses have been proposed, among which neuroinflammation is now emerging to be relevant in CIPN pathophysiology. In this review, we consider different aspects of neuro-immune interactions in several CIPN preclinical studies which suggest a critical connection between chemotherapeutic agents and neurotoxicity. The features of the neuroinflammatory processes may be different depending on the type of drug (platinum derivatives, taxanes, vinca alkaloids and proteasome inhibitors). In particular, recent studies have demonstrated an involvement of the immune response (both innate and adaptive) and the stimulation and secretion of mediators (cytokines and chemokines) that may be responsible for the painful symptoms, whereas glial cells such as satellite and Schwann cells might contribute to the maintenance of the neuroinflammatory process in DRG and axons respectively. Moreover, neuroinflammatory components have also been shown in the spinal cord with microglia and astrocytes playing an important role in CIPN development. Taking together, better understanding of these aspects would permit the development of possible strategies in order to improve the management of CIPN.